Ruptured thoracic aortic aneurysm in patient with systemic lupus erythematosus - Conti,Daniel Oliveira De (2011)
It is reported a ruptured descending thoracic aortic aneurysm in a 25-year-old systemic lupus erythematosus woman who underwent 19 years steroid therapy. She was treated with 2 endovascular stent-grafts, discharged from hospital 13 days after the procedure in good health. Three months later she returned with hemorrhagic shock due to high digestive hemorrhage secondary to an aortic-esophageal fistula. She underwent to an open emergency surgery, and died during the post-operative period.